2022
DOI: 10.3389/fcell.2022.921503
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional expression of m6A and m5C RNA methyltransferase genes in the brain and fat body of honey bee adult workers

Abstract: Honey bee (Apis mellifera) adult workers change behaviors and nutrition according to age progression. Young workers, such as nurses, perform in-hive tasks and consume protein-rich pollen, while older workers (foragers) leave the colony to search for food, and consume carbohydrate-rich nectar. These environmentally stimulated events involve transcriptional and DNA epigenetic marks alterations in worker tissues. However, post-transcriptional RNA modifications (epitranscriptomics) are still poorly explored in bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 74 publications
2
4
0
5
Order By: Relevance
“…In a previous study, we found that labour division has an inherent genetic basis that can be controlled by Sifor or miR-279c-5p in red fire ants (Chen et al, 2022;. RNA epigenetics serve as an important manifestation of remodelled gene (Bataglia et al, 2021(Bataglia et al, , 2022, consistent with the results of this study. However, these reports are only descriptive in terms of the overall m 6 A levels of RNA, indicating a potential function, but not a described mechanism.…”
Section: Dopamine Regulated By M 6 a Modification Correlated With Lab...supporting
confidence: 91%
See 3 more Smart Citations
“…In a previous study, we found that labour division has an inherent genetic basis that can be controlled by Sifor or miR-279c-5p in red fire ants (Chen et al, 2022;. RNA epigenetics serve as an important manifestation of remodelled gene (Bataglia et al, 2021(Bataglia et al, , 2022, consistent with the results of this study. However, these reports are only descriptive in terms of the overall m 6 A levels of RNA, indicating a potential function, but not a described mechanism.…”
Section: Dopamine Regulated By M 6 a Modification Correlated With Lab...supporting
confidence: 91%
“…The components of the m 6 A writer complex are involved in mRNA methylation in humans; however, their role in social insects is not well understood. A previous study showed that METTL3, DNMT2, NOP2, NSUN2, NSUN5 and NSUN7 transcripts were expressed at higher levels in the brains of foragers than in younger honeybees (Bataglia et al., 2022). In our study, we found that foragers had significantly higher expression levels of Mettl3 , Mettl14 , Wtap , and Vir than nurses (Figure 2c).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The studies further indicated that m 6 A methylation is involved in viral infection and sperm tail formation in the mosquitoes, respectively. In addition, existence of m 6 A machinery was demonstrated in the honey bee Apis mellifera with m 6 A levels significantly different between 4th larval instars of worker and queen bees (Bataglia, Simões, & Nunes, 2021;Bataglia, Simões, & Nunes, 2022;Wang et al, 2021). While m 6 A readers and writers have been reported from D. melanogaster, B. mori, A. mellifera, Ae.…”
Section: Introductionmentioning
confidence: 99%